2014
DOI: 10.1186/1758-5996-6-80
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid as a pleiotropic compound with potential therapeutic use in diabetes and other chronic diseases

Abstract: Alpha-lipoic acid is a naturally occurring substance, essential for the function of different enzymes that take part in mitochondria’s oxidative metabolism. It is believed that alpha-lipoic acid or its reduced form, dihydrolipoic acid have many biochemical functions acting as biological antioxidants, as metal chelators, reducers of the oxidized forms of other antioxidant agents such as vitamin C and E, and modulator of the signaling transduction of several pathways. These above-mentioned actions have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
175
0
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(194 citation statements)
references
References 161 publications
(271 reference statements)
3
175
0
16
Order By: Relevance
“…ALA rapidly crosses the cell membranes, cytosol and blood-brain barrier. Due to amphiphilic properties, ALA has more advantages compared with other antioxidants such as vitamin C and E. Interestingly, Lipoic acid and its reduced form, dihydrolipoic acid (DHLA) has a redox potential of −0.32 V while the redox potential of GSH/ GSSG is −0.24 V. This difference reflects the fact that ALA has a greater defense capacity against oxidative damage than does GSH and ALA is able to reduce oxidized glutathione to GSH (Dwivedi et al 2014;Gomes and Negrato 2014;Rochette et al 2013;Smith et al 2004). It displays antioxidant effects by scavenging ROS and regenerates other endogenous oxidized antioxidants to their active reduced form (Hussein et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…ALA rapidly crosses the cell membranes, cytosol and blood-brain barrier. Due to amphiphilic properties, ALA has more advantages compared with other antioxidants such as vitamin C and E. Interestingly, Lipoic acid and its reduced form, dihydrolipoic acid (DHLA) has a redox potential of −0.32 V while the redox potential of GSH/ GSSG is −0.24 V. This difference reflects the fact that ALA has a greater defense capacity against oxidative damage than does GSH and ALA is able to reduce oxidized glutathione to GSH (Dwivedi et al 2014;Gomes and Negrato 2014;Rochette et al 2013;Smith et al 2004). It displays antioxidant effects by scavenging ROS and regenerates other endogenous oxidized antioxidants to their active reduced form (Hussein et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous researchers have reported the effects of many organic or inorganic compounds on various organs, leading to disorders such as fatty liver or diabetic nephropathy (5,6). Furthermore, other studies have reported that some compounds, even known as beneficial food materials, can worsen a disease condition (7,8).…”
mentioning
confidence: 99%
“…Перші випадки терапевтичного застосування α-ЛК описали 1959 року в Німеччині E. Bock та J. Schneeweiss -для лікування хворих із гострим отруєнням грибами Аmanita phalloides. А невдовзі ті самі автори виявили лікувальні властивості α-ЛК при невропатіях [1].…”
Section: вступunclassified
“…У наш час α-ЛК та її відновленій хімічній формі -дигідроліпоєвій кислоті приписують низку корисних біохімічних та епігенетичних властивостей: вони діють як універсальні антиоксиданти, здатні відновлювати окислені форми інших ферментів антиоксидантного захисту організму, а також модулюють численні внутрішньоклітинні сигнальні шляхи, зокрема інсуліновий та ядерний фактор каппа В (NFkB) [1,2]. Перераховані властивості, а також безпека α-ЛК як ендогенного метаболіту організму людини обгрунтовують напрямок вивчення препаратів на її основі при лікуванні захворювань, у патогенезі яких важливу роль відіграють оксидантний стрес, інсулінорезистентність та системна запальна відповідь, зокрема -цукрового діабету (ЦД) та його ускладнень.…”
Section: вступunclassified
See 1 more Smart Citation